2015
DOI: 10.1002/app.42863
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐modified MgO nanoparticle enhances the mechanical and direct‐current electrical characteristics of polypropylene/polyolefin elastomer nanodielectrics

Abstract: Polypropylene (PP)/polyolefin elastomer (POE) blends and MgO/PP/POE nanocomposites were fabricated by melt blending. The morphology, mechanical, and electrical properties of the nanocomposites were investigated. Scanning electron microscopy showed that the surface-modified MgO nanoparticles were well dispersed in the polymer matrix at low loadings of less than 3 phr. X-ray diffraction demonstrated that the crystalline phases of PP in the composites were changed and that the b phase significantly increased. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 54 publications
5
60
0
Order By: Relevance
“…They found that blending PP with POE can result in enhanced mechanical flexibility, good enough thermal properties (i.e., high melting temperatures) and enhanced electrical properties (i.e., increased volume resistivity and high breakdown strength) which is promising for HVDC cable. However, the space charge accumulation were deteriorated and further work by them revealed that introducing MgO nanoparticles could improve the electrical properties of PP/POE blends, especially space charge accumulation. Nanocomposites consisting of PP/POE blends and SiO 2 nanoparticles were prepared by Diao et al and the influence of nanoparticle addition on the mechanical, thermal and DC electrical properties of the nanocomposites were investigated.…”
Section: The Emergence Of Thermoplastic Elastomer In Electrical Insulmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that blending PP with POE can result in enhanced mechanical flexibility, good enough thermal properties (i.e., high melting temperatures) and enhanced electrical properties (i.e., increased volume resistivity and high breakdown strength) which is promising for HVDC cable. However, the space charge accumulation were deteriorated and further work by them revealed that introducing MgO nanoparticles could improve the electrical properties of PP/POE blends, especially space charge accumulation. Nanocomposites consisting of PP/POE blends and SiO 2 nanoparticles were prepared by Diao et al and the influence of nanoparticle addition on the mechanical, thermal and DC electrical properties of the nanocomposites were investigated.…”
Section: The Emergence Of Thermoplastic Elastomer In Electrical Insulmentioning
confidence: 99%
“…This includes the use of surfactants, which help to reduce high surface energy and interfacial tension in nanofillers . Improvement in dielectric properties such as AC and DC breakdown strength , electrical and water tree resistance as well as reduction in the space charge , partial discharge , permittivity and dielectric loss has been widely documented in nanocomposites with chemically treated nanoparticles.…”
Section: Application Of Micro and Nano‐size Filler In High Voltage Inmentioning
confidence: 99%
“…Polymeric nanocomposites (PNCs) have been the subject of intense research in materials sciences for the last 2 decades because of the ability of these materials to integrate the useful properties of both polymers and inorganic nanofillers (nanoparticles, nanotubes, nanowires, and nanoplatelets) . Polymers have advantages of processability, flexibility, ductility, and electrical insulation, whereas rigidity, thermal stability, barrier properties, and flame retardancy are the major useful properties of nanofillers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, PNC materials based on poly(vinyl alcohol) (PVA) and titanium dioxide (i.e., titania or TiO 2 ) have made considerable academic and technological progress because of their wide range of applications in various fields . PVA is a hydrophilic, nontoxic, and biocompatible polymer, and it is completely soluble in hot water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation